PENGEMBANGAN PEMBELAJARAN VIRTUAL BERBASIS GOOGLE CLASSROOM UNTUK MENINGKATKAN PRESTASI BELAJAR ( Studi Pengembangan pada Mata Pelajaran Biologi Kelas XI MIPA di SMA Negeri 1 Pagar Alam ) - Henny Hairahmah; Bambang Sahono (DIADIK, 2021)
This study aims to describe the development of virtual learning based on google classroom  that is feasible in improving student learning achievement, and describe the effectiveness of virtual learning based on google classroom has been developed to improve learning achievement on Biology subjects in class XI Mipa SMA Negeri 1 Pagar Alam. The research design used is development research  or (Research and Development). with the subject of student in class XI MIPA SMA Negeri 1 Pagar Alam. Data collection techniques used in the study were assessment sheets and student test results. The data analysis used mean and t-test. The validation instrument for material experts and media experts in research is the Likert scale. The conclusions of this research are virtual  learning based on Google Classroom which is developed is feasible to improve learning achievement in the Excretion system material in humans, and the development of virtual learning based on Google Classroom is effective in improving learning achievement based on the results of limited trials and broad scale trials of class XI students of MIPA SMAN 1 Pagar Alam